Pengembangan Media Pembelajaran Infografis berbasis Canva pada Siswa Kelas V Materi Persebaran Flora dan Fauna di Indonesia - Nadia Eka Putri; Ria Fajrin Rizqy Ana (Universitas Nusantara PGRI Kediri, 2024)
The background of this research is that many teachers only use the lecture method without the help of learning media when learning. This causes students to feel bored and sleepy in learning, in addition to the lack of interest in learning students. Therefore, it is necessary to use learning media that can overcome these obstacles and make learning more interesting and easier to understand. Especially in learning the subject of Science on the Distribution of Flora and Fauna in Indonesia. The purpose of this study is to describe the process, validity, and implementation of the development of Canva-based infographic learning media on the distribution of flora and fauna in Indonesia for grade V students at SDN I Pelem, Campurdarat District. This study uses the ADDIE development model. The results of the study showed validity with an average value of 79.51% with the category